2020
DOI: 10.3390/pharmacy8040205
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacy Students’ Perceptions and Stigma Surrounding Naloxone Use in Patients with Opioid Use Disorder: A Mixed Methods Evaluation

Abstract: Pharmacists represent a key group of healthcare professionals that can increase awareness and destigmatize naloxone use. The objective of this study was to investigate pharmacy student perceptions of the use, dispensing, and stigma surrounding naloxone. An electronic survey was administered to pharmacy students that included questions about demographics, work history, naloxone use, and naloxone stigma. Separate qualitative interviews were performed to identify themes surrounding naloxone use. Two-hundred sixty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Furthermore, recent recommendations from the American Association of Colleges of Pharmacy indicate that naloxone counseling and overdose management should be core components of the Doctor of Pharmacy curriculum 15 . The current literature highlights several innovative naloxone training programs; however, the majority focus on student's perceived self‐efficacy in counseling as the primary outcome 8‐11 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, recent recommendations from the American Association of Colleges of Pharmacy indicate that naloxone counseling and overdose management should be core components of the Doctor of Pharmacy curriculum 15 . The current literature highlights several innovative naloxone training programs; however, the majority focus on student's perceived self‐efficacy in counseling as the primary outcome 8‐11 …”
Section: Discussionmentioning
confidence: 99%
“…In response to the passage of naloxone specific state legislation, several Doctor of Pharmacy programs began incorporating naloxone training as part of the required curriculum 7 . Much of the literature focuses on training student pharmacists through a combination of traditional lecture and active learning in a lab environment or experiential setting, followed by an assessment of perceived confidence in the ability to counsel on naloxone use 8‐11 . While self‐confidence in one's ability to counsel is important, there is little evidence highlighting the impact of a specific training format on the ability to effectively counsel a patient on naloxone use.…”
Section: Introductionmentioning
confidence: 99%
“…Naloxone stigma is still undefined, despite its use in academic literature. 38-40 To define naloxone stigma within a scope applicable to patients, pharmacists, and prescribers, based on relevant studies, 17,20-23 the pertinent individual stigma variants, including perceived stigma (awareness) and personal stigma (agreement) are considered (Table 1). Self-stigma (concurrence) is only applicable to patients since they are “the stigmatized.” 34,36 Even then, this may be debatable because, unlike mental illness and OUD, 32,34,36,41 patients can choose to distance themselves from naloxone.…”
Section: What Is Stigma?mentioning
confidence: 99%
“…For example, a recent study investigating stigma-related barriers to naloxone recommendations by student pharmacists found that although stigma was seen among students, it was also perceived to be present amongst patients as well -limiting the patients' willingness to receive a naloxone recommendation. 10 Although work has been done to reduce OUD stigma, research suggests that educators may still have an incomplete picture of health professional students and stigma, and therefore strategies by which to overcome it. For example, one U.S. college of nursing implemented an interactive presentation on OUD.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a recent study investigating stigma-related barriers to naloxone recommendations by student pharmacists found that although stigma was seen among students, it was also perceived to be present amongst patients as well – limiting the patients’ willingness to receive a naloxone recommendation. 10 …”
Section: Introductionmentioning
confidence: 99%